Tectonic dynamics of the Zhongjiannan Basin in the western South China Sea since the late Miocene - Yin, Zhengxin; Cai, Zhourong; Yao, Yongjian; Huang, Qianru; Li, Zhengyuan (Frontiers in Earth Science, 2023)
The Zhongjiannan Basin is located west of the South China Sea (SCS) and was affected by the left-lateral strike-slip of the Red River Fault (RRF), the West Edge Fault of the South China Sea (WEFSCS) and the continental rifting of the South China Sea in the early Cenozoic. The Zhongjiannan Basin formed in a strike-pull basin with an S‒N distribution. During the middle Miocene, the sea spreading of the SCS stopped, but the dynamic mechanism of the Zhongjiannan Basin, which controlled the sedimentary and the structural evolution after the late Miocene, remains unclear. In this paper, through the segment interpretation of the latest seismic section in the Zhongjiannan Basin, we conduct a comparative study of the sedimentary structure in the southern and northern Zhongjiannan Basin since the late Miocene. Combined with the regional tectonic dynamics analysis, we propose that the sedimentary and structural evolution of the Zhongjiannan Basin since the late Miocene was mainly controlled by residual magmatic activity in the Southwest Subbasin (SWSB) after expansion stopped, and the compressional structure stress field weakened gradually from south to north. The compressional tectonic stress field from north to south was formed in the northern basin under the dextral strike-slip movement of the RRF. The sedimentary and structural environment was relatively stable in the middle basin. Therefore, the sedimentary-structure evolution of the Zhongjiannan Basin since the late Miocene was controlled by the two different structural stress fields. The above knowledge not only has guiding significance for oil and gas exploration in the Zhongjiannan Basin but also provides a reference for studying the initiation time of dextral strike-slip along the Red River Fault Zone, as well as the junction position between the RRF and the WEFSCS.